Bridging skills demand and supply in South Africa: the role of public and private intermediaries - Petersen, Il-Haam; Kruss, Glenda; McGrath, Simon; Gastrow, Michael (Routledge, 2016)
Demand-led skills development requires linkages and coordination between firms and education and training organisations, which are major challenges considering that each represents a ‘self-interested’ entity. The need for a ‘collaborative project’ involving government, firms, universities and colleges, and other bodies is thus increasingly recognised. However, the crucial role of intermediaries has been largely overlooked. The article addresses this gap by investigating the main roles of public and private intermediaries across three case studies: sugarcane growing and milling, automotive component manufacturing, and the Square Kilometre Array sectoral systems of innovation. The research highlights the need for a move towards systemic thinking, to bridge across public and private objectives. It shows that private intermediaries play a larger role than is recognised in policy; that public–private intermediaries play crucial roles in coordination; and the potential for public intermediaries to contribute more effectively to systemic functioning.